Heterogeneous experiences of people with bipolar disorder during euthymia: Profiles of global remission and personal recovery. - Munuera, Caroline; Compagnone, Philippe; Gard, Sébastien; Chevrier, François; Chevrier, Basilie; M'Bailara, Katia (British Journal of Clinical Psychology, 2025)
Objectives: Clinical heterogeneity is a major problem in mental health, referring to wide clinical variability among people with the same diagnosis. In bipolar disorders (BD), an heterogeneity was found both in global remission (symptomatic and functional) and in personal recovery during euthymia. This heterogeneity is a challenge for clinicians, who have to adapt their care to the individuals' characteristics. This preliminary study aimed at identifying profiles of experiences during euthymia by considering global remission (manic and depressive symptomatology, and functional impairment) and personal recovery, and exploring personal and contextual correlates associated with the heterogeneity of experiences. Methods: A convenience sample of 58 participants in euthymia of BD was recruited. Data were collected using self‐report questionnaires. Consistent with a person‐oriented approach, clustering was performed to identify profiles by simultaneously considering symptomatology, functional impairment, and personal recovery. Associations between the identified profiles and socio‐demographic, clinical, and family characteristics were explored using analysis of variance, Fisher's exact tests, and post hoc tests. Results: Five profiles were identified when considering both global remission and personal recovery: adverse experience (20.69%), slightly adverse experience (22.41%), unbalanced experience (10.34%), positive experience (22.14%), and hyperthymic positive experience (24.14%). Among the correlates, only current family functioning was significantly associated with the identified profiles through cohesion, communication, and satisfaction dimensions. Conclusions: These results highlight that personal recovery and family dynamics of people with BD should be more considered in the clinical practice to better understand their experience during euthymia and adapt therapeutic care accordingly.